Diagnosis of the Golden Indonesia Scenario 2045 Through an Integrated Reality Theory (IRT) Approach: Systemic Analysis of Bureaucratic Entropy as a Critical Variable - La Himmah il Princess Choris; M. Shoim (CV. Era Digital Nusantara, 2026)
This study aims to analyze the scenario of achieving Golden Indonesia 2045 through the perspective of Integrated Reality Theory (IRT)—a framework developed to diagnose the performance of socio-economic systems based on five fundamental variables: Energy (E), Information (I), Entropy (S), Consciousness (C), and Rate of Evolution (v). In contrast to conventional growth approaches that emphasize physical capital accumulation, IRT positions entropy as a divisive variable that determines the effectiveness of all development inputs. Through qualitative analysis with a conceptual-comparative approach, this study finds that Indonesia's success in achieving developed country status by 2045 does not depend on the addition of energy (E) alone, but on the system's ability to suppress bureaucratic entropy—which is manifested in corruption, budget inefficiency, regulatory overlap, and sectoral ego—to close to zero. Without systemic intervention on the entropy variable, the Demographic Bonus and the downstream of natural resources will experience systemic stagnation. These findings imply the need for a shift in policy orientation from economic expansion towards comprehensive structural cleansing, including the establishment of national entropy measurement instruments.